2021
DOI: 10.1186/s12967-021-02766-w
|View full text |Cite|
|
Sign up to set email alerts
|

M2 macrophage-derived exosomal microRNAs inhibit cell migration and invasion in gliomas through PI3K/AKT/mTOR signaling pathway

Abstract: Background Glioma, the most common primary brain tumor, account Preparing figures for 30 to 40% of all intracranial tumors. Herein, we aimed to study the effects of M2 macrophage-derived exosomal microRNAs (miRNAs) on glioma cells. Methods First, we identified seven differentially expressed miRNAs in infiltrating macrophages and detected the expression of these seven miRNAs in M2 macrophages. We then selected hsa-miR-15a-5p (miR-15a) and hsa-miR-92… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…RAP1B is mainly located in the nucleus, and studies have shown that RAP1B expression is associated with tumorigenesis and metastasis in, for example, ovarian cancer, oesophageal squamous cell carcinoma, and gastric cancer, and can act as a tumour promoter by regulating multiple signalling pathways such as Wnt/β‐catenin, PI3K/AKT/mTOR pathway. 18 , 19 , 20 , 21 , 22 We confirmed that the overexpression of SNORA70E induced the expression of the RAP1B protein significantly. Through RIP detection, we found that DKC1 can bind to RAP1B mRNA, thus we suggest that SNORA70E regulates RAP1B mRNA through pseudouracil modification, affecting its protein expression.…”
Section: Discussionsupporting
confidence: 66%
“…RAP1B is mainly located in the nucleus, and studies have shown that RAP1B expression is associated with tumorigenesis and metastasis in, for example, ovarian cancer, oesophageal squamous cell carcinoma, and gastric cancer, and can act as a tumour promoter by regulating multiple signalling pathways such as Wnt/β‐catenin, PI3K/AKT/mTOR pathway. 18 , 19 , 20 , 21 , 22 We confirmed that the overexpression of SNORA70E induced the expression of the RAP1B protein significantly. Through RIP detection, we found that DKC1 can bind to RAP1B mRNA, thus we suggest that SNORA70E regulates RAP1B mRNA through pseudouracil modification, affecting its protein expression.…”
Section: Discussionsupporting
confidence: 66%
“…2-hydroxyglutarate (2HG) produced by IDH1/2 mutation promotes mTOR activity by depleting KDM4A and decreasing DEPTOR protein stability (128), presenting another mechanism of IDH1/2 mutation promoting the genesis of glioma and the possibility of a combination IDH inhibitor and mTOR inhibitor. Simultaneously, the pathway is a hotspot of studies on microRNA, lncRNA, and exosomes because of the extensive functions of noncoding RNA and PI3K/Akt (129)(130)(131)(132). In addition, the downstream targets of the pathway, such as p70S6K, 4EBP1, and eIF-4E, are also druggable targets (133).…”
Section: Pkcmentioning
confidence: 99%
“…It has been verified that M2 macrophages could secret miR-15a and miR-92a via exosomes, and subsequently, miR-15a and miR-92a separately repressed cyclin D1 (CCND1) and Ras-related protein Rap1b (Rap1b). Thus, the PI3K/AKT/mTOR signaling pathway was interfered, and glioma migration and invasion was suppressed (32).…”
Section: Exosomal Mirnas and Invasion/migration Of Gliomamentioning
confidence: 99%